Integrated Reporting and Enterprise Value of Consumer Goods Companies Listed on Nigerian Exchange Group - Abiodun, Olatunde; Siyanbola , Tunji Trimisiu; Odewole , Olabisi Bolarinwa (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study investigates the effect of integrated reporting (IR) on enterprise value (EV), incorporating corporate governance (CG) as a moderating factor, using a balanced panel dataset of 20 firms listed on the Nigerian Exchange Group (NGX) spanning 2015 to 2024, with data extracted from firms’ annual reports. The Hausman specification test guided the selection of the fixed effects (FE) panel regression model for the study. The findings reveal that disclosures on performance (PER), governance (GOV), strategy and resource allocation (SRA), organizational overview and external environment (OEE), outlook (OUT), and risks and opportunities (RO) significantly increase EV. Conversely, business model (BM) and basis of preparation and presentation (BPP) disclosures show no significant influence, reflecting limited investor focus in Nigeria’s voluntary IR context. CG independently enhances EV and, importantly, moderates the IR–EV relationship: strong governance amplifies the positive valuation impact of integrated reporting. Implying that firms with superior governance quality experience greater market valuation benefits from IR, highlighting governance as a critical factor that reinforces investor confidence and maximizes the value relevance of integrated reporting. The study concludes that IR, especially through performance and governance reporting, has a strong influence on the amount of enterprise value, and corporate governance reinforces the confidence of the investors and acts as a validator of credibility. To realise the maximum benefits of enhancing enterprise value, it is recommended that firms focus on strong and stakeholder-oriented reporting in these vital areas that align with known international standards, including that of the IIRC (2021) framework.
Keywords: Integrated Reporting; Enterprise Value; Corporate Governance; Voluntary Disclosure; Financial Transparency